Self-management perspectives of elderly patients with multimorbidity and practitioners - status, challenges and further support needed? - Breckner, Amanda; Roth, Catharina; Glassen, Katharina; Wensing, Michel (BMC family practice, 2021)
Patients with multimorbidity (here defined as three or more chronic conditions) require constant treatment and care. Furthermore, they have to manage their health and diseases in daily life. Offering support to patients’ medical self-management is an important task of primary care. The aim of this study was to explore, what further support is needed from the perspective of patients’ and primary care practitioners.
Gesehen am 16.12.2021